2007
DOI: 10.1598/jaal.50.6.5
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Teacher Identity: Exploring the Use of Electronic Teaching Portfolios With Preservice English Teachers

Abstract: Electronic portfolio use within the context of a teacher education program is explored in this article. Although the use of e‐portfolios has emerged as a topic that integrates new technologies and the education of preservice teachers, little work thus far has documented the complexities involved in the authoring process of e‐portfolios. To address this gap, this article focuses on two preservice teachers' processes of crafting e‐portfolios. Specifically, the article documents the realities of presenting onesel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 4 publications
0
9
0
4
Order By: Relevance
“…Looking at reflective journals as a means to explore three PTs’ evolving teacher identities, Hinchion (2017) highlighted the role participatory learning played in PTs’ identity formations. Hallman (2007) showed tensions in the ways PTs presented themselves in electronic teaching portfolios. Although PTs wanted to appear competent to professional audiences, they also wanted to present themselves as continually developing and inquiring into their teaching roles, a stance their university professor advocated.…”
Section: Resultsmentioning
confidence: 99%
“…Looking at reflective journals as a means to explore three PTs’ evolving teacher identities, Hinchion (2017) highlighted the role participatory learning played in PTs’ identity formations. Hallman (2007) showed tensions in the ways PTs presented themselves in electronic teaching portfolios. Although PTs wanted to appear competent to professional audiences, they also wanted to present themselves as continually developing and inquiring into their teaching roles, a stance their university professor advocated.…”
Section: Resultsmentioning
confidence: 99%
“…Portfolios are believed to unobtrusively document events through classroom artifacts gathered by instructors and support personnel (Habib & Wittek, 2007;Zepeda, 2002). Since the mid 1980s many teacher education programs turned to portfolios to document teacher practice and growth; promote inquiry, reflection, and skill development; and assess competency (Dhonau & McApline, 2005;Hallman, 2007;Rickards et al, 2008;. Land and Zembal-Saul (2003) found that portfolios documented the thought processes of 20 preservice teachers who were exploring properties of light (e.g., reflection, refraction).…”
Section: Portfolios To Capture and Evaluate Teachingmentioning
confidence: 99%
“…The Internet provides an open and interactive environment in which people can assert their uniqueness while connecting with like-minded communities. These people create a self-presentation on weblogs or e-portfolios as a means to explore or to develop an identity (Hallman, 2007). According to whether people have engaged in an identity-exploring process and have made a commitment in this regard or not, Marcia (1966Marcia ( , 1980 proposed four identity stages: identity achievement (those who have explored and committed), moratorium (those who are exploring and vaguely committed), foreclosure (those who have committed without experiencing the exploring process) and identity diffusion (those who have neither experienced the process nor committed).…”
Section: Identity and Career Commitmentmentioning
confidence: 99%